2023
DOI: 10.1111/jcmm.18039
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia increased the expression of ESM1 and ICAM‐1 in vascular endothelial cells via the downregulation of microRNA‐181a1

Shin Takasawa,
Mai Makino,
Akiyo Yamauchi
et al.

Abstract: Sleep apnea syndrome (SAS) exposes cells throughout the body to intermittent hypoxia (IH). Intermittent hypoxia is a risk factor not only for hypertension and insulin resistance but also for vascular dysfunction. We have reported correlations between IH, insulin resistance and hypertension. However, the details of why IH leads to vascular dysfunction remain unclear. In this study, we investigated inflammation‐related transcripts in vascular endothelial cells (human HUEhT‐1 and mouse UV2) exposed to IH by real‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…We conducted additional investigation into the pathways through which IH increased the mRNA levels of both Icam-1 and Esm1. We also identified a potential post-transcriptional mechanism involving miR-181a1-mediated expression [133] (Figure 5).…”
Section: Cardiovascular Factors For Hypertension In Ihmentioning
confidence: 97%
See 2 more Smart Citations
“…We conducted additional investigation into the pathways through which IH increased the mRNA levels of both Icam-1 and Esm1. We also identified a potential post-transcriptional mechanism involving miR-181a1-mediated expression [133] (Figure 5).…”
Section: Cardiovascular Factors For Hypertension In Ihmentioning
confidence: 97%
“…Therefore, the increases in pro-inflammatory and inflammatory cytokines such as IL-1β, IL-6, and IL-8 in monocytes lead to systemic inflammation and worsen metabolic syndrome, including hypertension in SAS patients (Figure 6). It is suggested that, in patients with SAS, the increased expression of Esm1 and Icam-1 in vascular endothelial cells may contribute to the development of vascular endothelial dysfunction, while miR-181a1 may have a significant impact on the modulation of these gene expressions [133]. The up and down arrows next to the name indicate increase and decrease, respectively.…”
Section: Pro-inflammatory/inflammatory Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation